Supercomputer Simulations of Fluid-Structure Interaction Problems Using an Immersed Boundary Method - Zhdanova, Natalya S.; Gorobets, Andrey V.; Abalakin, Ilya V. (Supercomputing Frontiers and Innovations, 2018)
The paper describes a supercomputer application in simulations of fluid-structure interaction problems. A compressible flow solver based on a high-accuracy scheme for unstructured hybrid meshes is considered. It combines an immersed boundary method with a dynamic mesh adaptation method in order to represent motion of solid objects in a turbulent flow. The use of immersed boundaries allows you to dynamically adapt the mesh resolution near moving solid surfaces without changing the mesh topology. Multilevel MPI + OpenMP parallelization of these components fits well with the architecture of modern cluster systems. The proposed implementation can engage thousands of CPU cores in one simulation efficiently. An example application is presented in which a high-speed turbulent flow around a cavity with a deflector is simulated.